Territorial behaviour and vocalisations of African Rock Pipit Anthus crenatus at Lundin's Neck, Barkly East - de Swardt, Dawid H (Biodiversity Observations, 2014)
During this vocalisation the bird's whole body was observed to vibrate extensively ...